(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
The armed forces have played an important role in the progress and setbacks of democratic politics in Latin America. The return to democracy and the consolidation of these democratic regimes in the past thirty years leads us to consider how Latin Americans see the new role that the armed forces have to develop in the regional context. To do this, we have analysed data from four regional polls: the 2011 Latinobarómetro Report, LAPOP Public Opinion Project reports, the research conducted by FLACSO in 2010 and the University of Salamanca’s survey data on the parliamentary elite. These all show us, although with some differences, that the armed forces continue to enjoy significant support and confidence among the citizens of Latin America. Citizens show great support for the Armed Forces, highlighting their work with human rights, their role in natural disasters, their organisational and training skills and performance in the context of high levels of crime